2015
DOI: 10.5732/cjc.014.10289
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/Akt/mTOR pathway in ovarian cancer: therapeutic opportunities and challenges

Abstract: The phosphatidylinositol 3 kinase (PI3K) pathway is frequently altered in cancer, including ovarian cancer (OC). Unfortunately, despite a sound biological rationale and encouraging activity in preclinical models, trials of first-generation inhibitors of mammalian target of rapamycin (mTOR) in OC have demonstrated negative results. The lack of patient selection as well as resistance to selective mTOR complex-1 (mTORC1) inhibitors could explain the disappointing results thus far. Nonetheless, a number of novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(175 citation statements)
references
References 71 publications
5
167
0
3
Order By: Relevance
“…For example Figure 7B showed that AKT1 was using the adapter proteins CALM1 to influence the downstream signals IRS1. This is due to the used transcription factors, which shown to also mainly interact with AKT and similar networks missing ERK effects were painted [59,83,84] and was previously shown in literature [56,85]. Something similar was also shown for the ERK action on IRS1 [86].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For example Figure 7B showed that AKT1 was using the adapter proteins CALM1 to influence the downstream signals IRS1. This is due to the used transcription factors, which shown to also mainly interact with AKT and similar networks missing ERK effects were painted [59,83,84] and was previously shown in literature [56,85]. Something similar was also shown for the ERK action on IRS1 [86].…”
Section: Discussionsupporting
confidence: 66%
“…The algorithm mainly shows two properties: (i) It nicely finds the interaction of phosphorylating and proteolytic signaling molecules, (ii) however it struggles to find interactions between signaling molecules and transcription factors. While the action of AKT on transcription factors is well described [59], the action of ERK on transcription factors could not be reconstructed as in the network of Klinger et al [34].…”
Section: Using Multienrichment Gene Sets Revealed a Comprehensive Netmentioning
confidence: 99%
“…Numerous signaling molecules of the PI3K/Akt/mTOR pathway have oncogenic properties and constitutive activation of this signaling pathway is often involved in the progression of various human cancers (34,35). Contrary to tumor suppressor genes such as PTEN and p53 which can stimulate autophagy, oncogenes of PI3K and Akt have been confirmed to play an inhibiting role in autophagy activation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PTEN has gained particular attention for its critical role in multiple types of cancer. Numerous previous studies have demonstrated that low expression levels of PTEN were associated with poor prognosis and chemoresistance in OC (35,36).…”
Section: Discussionmentioning
confidence: 99%